MICROMERITIC CHARACTERISTIC OF SPHERICAL AGGLOMERATED ACETAMINOPHEN CRYSTAL BY SPHERICAL NEUTRALIZATION METHOD - Tuslinah, Lilis (Sekolah Tinggi Farmasi Bandung, 2015)
Direct tableting method needs to increase compressibility and flowability of the bulk powder in order to maintain a steady supply of powder mixture to tableting machine and sufficient mechanical strength of compacted tablet. Acetaminophen exhibits poor water solubility and flow properties.Spherical agglomerates of acetaminophen were prepared by neutralization method. Spherical agglomerates were characterized by differential scanning calorimetry, Infrared spectroscopy and X-ray diffactometry. Micromeritic behavior of pure and spherical agglomerates  of acetaminophen were carried out. Spherical agglomerates exhibited improved micromeritic properties compared with pure Acetaminophen.